Doação de leite humano no período pandêmico em um banco de leite humano de um hospital de referência do estado do Pará - SILVA, Ana Júlia Melo da (2023)
There are special situations in which the hospitalization of the infant has no conditions for sucking milk to the pregnant mother. Therefore, collecting human milk from the mother is essential to perform milk for her baby. However, when the mother has a less lactate production, it is recommended to pay attention to pasteurized human milk from human milk banks (HMB). The COVID-19 pandemic is having an impact across the globe, including at HMB, putting donations in jeopardy. So, the objective of this subject is to show aspects of human milk donations in the period before and after Covid-19 in a reference to HMB in the state of Pará. The study is a descriptive cross sectional study spanning two different time periods. Statistical analyses and measures of central tendency were performed and it was found that in Covid 19 period less vol ume of human milk and more missed for non-conformities concerning the pandemic period were found. Conversely, this decrease (5.16%) is not as high as the previous studies as it is justified by the donation of human milk during this period. Thus, any promotion of information must give human milk and educational activities that give the donor instructions about milking and collecting. By doing this, any unconfirmed milk loss does not occur frequently and may give to all newborns that need it.